Cyclic adenosine monophosphate/phosphodiesterase 4 pathway associated with immune infiltration and PD-L1 expression in lung adenocarcinoma cells - Tong, Ling; Shan, Minjie; Zou, Wen; Liu, XianLing; Felsher, Dean W.; Wang, Jingjing (Frontiers in Oncology, 2022)
Background. The cyclic adenosine monophosphate/phosphodiesterase 4 (cAMP/PDE4) pathway is involved in inflammation and immune regulation; however, the effect of cAMP/PDE4 on immune infiltration and immune evasion in lung adenocarcinoma (LUAD) remains unclear. Methods. CBioPortal, which is the The Cancer Genome Atlas (TCGA) online database, and the Kaplan Meier plotter were used to analyze the association between genes and the prognosis of TCGA-LUAD. Tumor Immune Estimation Resource (TIMER) was used to analyze the association between gene expression and immune infiltration. The Genecards database was used to identify the transcription factors of related genes. The lung adenocarcinoma cell line H1299 and A549 were treated with cAMP pathway drugs. Flow cytometry and qRT-PCR were used to detect the PD-L1 protein and gene expression, respectively. A one-way analysis of variance with Tukey’s post-hoc test or a Student’s t-test were used. Results. It was found that PDE4B and CREB1, which are downstream genes of the cAMP/PDE4 axis, were differentially expressed in LUAD and adjacent tissues and are correlated with the prognosis and immune infiltration of LUAD. In the CBioPortal database, cAMP pathway genes are closely related to programmed cell death-ligand 1 (PD-L1) expression in TCGA-LUAD. The protein-protein interaction revealed that there was a direct interaction between CREB1/CREBBP, which are the downstream molecules of the cAMP/PDE4 axis, and MYC; however, MYC was predicted to bind to the PD-L1 transcription site and regulate PD-L1 expression. CREB1 was also predicted to transcriptionally bind to both MYC and PD-L1. These results predicted the interaction network of cAMP/PDE4/CREB1/CREBP/MYC/PD-L1, and MYC is the core factor may be related to MYC. In the cell experiment, forskolin (an adenylate cyclase activator) and zardaverine (a PDE4 inhibitor) enhance the cAMP pathway and decrease PD-L1 expression, while SQ2253 (an adenylate cyclase inhibitor) inhibits the cAMP pathway and increases PD-L1 expression of the LUAD cell lines H1299 and A549, and MYC regulation by these drugs was positively correlated with PD-L1 regulation, which verified the regulation of the cAMP/PDE4 pathway on MYC and PD-L1. Conclusions. This study showed that the cAMP/PDE4 pathway may play an important role in PD-L1 regulation and immune infiltration in LUAD.